Wild-type Lactococcus lactis producing bacteriocin-like prophage lysins - Takala, Timo M.; Mokhtari, Samira; Ahonen, Susanna L.; Wan, Xing; Saris, Per E. J. (Frontiers in Microbiology, 2023)
In this paper, we present a wild-type Lactococcus lactis strain secreting prophage lysins, which behave like bacteriocins. Lactococcus is a genus of lactic acid bacteria used in dairy industry as a starter. Lactococci have been found to produce altogether more than 40 different bacteriocins, ribosomally synthesized antimicrobial proteins. All known Lactococcus spp. bacteriocins belong to classes I and II, mainly heat-resistant peptides. No class III bacteriocins, bigger heat-sensitive proteins, including phage tail-like bacteriocins, have been found from Lactococcus spp. Unlike phage tail-like bacteriocins, prophage lysins have not been regarded as bacteriocins, possibly because phage lysins contribute to autolysis degrading the host’s own cell wall. In this study, L. lactis strain LAC460, isolated from spontaneously fermented idli batter, was shown to kill other Lactococcus strains with protease- and heat-sensitive lytic activity. Three phage lysins were identified in the culture supernatant. The genes encoding the three lysins were localized in different prophage regions in the chromosome. By knock-out mutants, two of the lysins, namely LysL and LysP, were demonstrated to be responsible for the antimicrobial activity. The strain LAC460 was found to be resistant to the lytic action of its own culture supernatant, and as a consequence, the phage lysins could behave like bacteriocins targeting and killing other closely related bacteria. Hence, similar to phage tail-like bacteriocins, phage lysin-like bacteriocins could be regarded as a novel type of class III bacteriocins.